1990
DOI: 10.1172/jci114840
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of parathyroid hormone gene expression by hypocalcemia, hypercalcemia, and vitamin D in the rat.

Abstract: In vivo in the rat 1,25(OH)2D3 decreases and a low calcium increases PTH mRNA levels. We now report the effect of 3 and 8 wk of changes in dietary vitamin D and calcium on PTH mRNA levels. PTH mRNA levels were increased by 3 wk of calcium deficiency (five times), a vitamin D-deficient diet (two times), and combined deficiency (10 times), but not changed by high calcium. Vitamin D-deficient-diet rats' PTH mRNA did not decrease after a single large dose of 1,25(OH)2D3, but did decrease partially after repeated d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
89
0
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(93 citation statements)
references
References 26 publications
(23 reference statements)
3
89
0
1
Order By: Relevance
“…These approaches were proven successful in our study because calcium and phosphorus blood levels were maintained normal, and PTH levels were also maintained normal. The dose of calcitriol was pharmacologic, and thus direct suppression of PTH gene transcription (54,55) may have been an important component of maintaining normal PTH levels.…”
Section: Discussionmentioning
confidence: 99%
“…These approaches were proven successful in our study because calcium and phosphorus blood levels were maintained normal, and PTH levels were also maintained normal. The dose of calcitriol was pharmacologic, and thus direct suppression of PTH gene transcription (54,55) may have been an important component of maintaining normal PTH levels.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the downregulation of VDR by hypocalcemia resulted in impairment of the inhibitory action of CTR on parathyroid cell function. Other authors (5,7) have shown that the inhibition of PTHmRNA by CTR is relatively ineffective when serum Ca concentration is low. This finding could be related to the low VDR expression induced by low Ca.…”
Section: Discussionmentioning
confidence: 99%
“…Because CTR decreases parathyroid gene transcription of PTHmRNA, additional experiments were performed to evaluate whether the decrease in VDR expression induced by hypocalcemia prevented the normal downregulation of PTHm-RNA by CTR (5). Thus a bolus of CTR was administered to rats before induction of hypocalcemia while other rats received the bolus after 6 h of hypocalcemia (when VDR was already downregulated by hypocalcemia).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of the an extracellular calcium sensing receptor (CaSR) when [Ca 2ϩ ] e concentrations are high maintains the storage form of PTH in the parathyroid gland (3,4). Release of PTH from the parathyroid gland is a direct result of a decrease in serum [Ca 2ϩ ] e (5,6). PTH is a potent stimulus of 1,25-dihydroxyvitamin D 3 (1,25(OH) 2 D 3 ) biosynthesis in the kidney proximal convoluted tubule by its induction of 1␣-hydoxylation (7).…”
Section: Extracellular Ionized Calcium [Ca 2ϩmentioning
confidence: 99%